2013
DOI: 10.1002/hup.2318
|View full text |Cite
|
Sign up to set email alerts
|

Human psychobiology of MDMA or ‘Ecstasy’: an overview of 25 years of empirical research

Abstract: The damaging effects of Ecstasy/MDMA are far more widespread than was realized a few years ago, with new neuropsychobiological deficits still emerging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
167
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(172 citation statements)
references
References 151 publications
(249 reference statements)
3
167
0
2
Order By: Relevance
“…While some proponents recommend MDMA at 1.5-1.7 mg/kg for treatment of PTSD Vollenweider et al, 2002), recreational users generally consume ϳ1.0 -3.0 mg/kg (Baylen and Rosenberg, 2006;Dumont and Verkes, 2006;Parrott, 2013). It is not unusual, however, for experienced MDMA users to take higher doses in an attempt to overcome tolerance to the drug's subjective effects (Parrott, 2013). Similar to the slow development of hyperthermia in rats, the desired psychoactive effects of oral MDMA in human users develop with relatively long latencies that could lead to multiple drug dosing.…”
Section: Translational Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…While some proponents recommend MDMA at 1.5-1.7 mg/kg for treatment of PTSD Vollenweider et al, 2002), recreational users generally consume ϳ1.0 -3.0 mg/kg (Baylen and Rosenberg, 2006;Dumont and Verkes, 2006;Parrott, 2013). It is not unusual, however, for experienced MDMA users to take higher doses in an attempt to overcome tolerance to the drug's subjective effects (Parrott, 2013). Similar to the slow development of hyperthermia in rats, the desired psychoactive effects of oral MDMA in human users develop with relatively long latencies that could lead to multiple drug dosing.…”
Section: Translational Relevancementioning
confidence: 99%
“…MDMA is a Schedule I controlled substance in the United States and under similar restrictions in most Western countries, but whether MDMA is harmful remains a contentious issue (Pentney, 2001;Check, 2004;Parrott, 2013). Initial studies in human and laboratory animals showed that MDMA exposure can induce life-threatening health complications, including fatal hyperthermia (Gordon et al, 1991;Ricaurte et al, 2000;Kalant, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…These highly variable MDMA-induced temperature responses, ranging from barely detectable increases to pathological hyperthermia, are also typical in humans; the same drug dose could have minimal or no adverse effects in some individuals, but serious life-threatening complications in others (Kalant, 2001;Parrott, 2013a). Our study focused on acute MDMA intoxication, but heightened brain temperature can also cause long-term changes in neural functions, as found in both preclinical studies and human research (Malberg and Seiden, 1998;Parrott and Young, 2014).…”
Section: Conclusion and Translational Relevancementioning
confidence: 99%
“…In humans, MDMA-related reductions of 5-HT transporters in different regions of the basal ganglia and the neocortex have been reported analogously (for review see Roberts et al, 2016b). Over the past three decades, the behavioral effects of MDMA use have been investigated extensively, and a broad range of cognitive dysfunctions has been reported in long-term MDMA users (Parrott, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…While declarative memory impairments have been consistently shown in MDMA users with moderate to large effect sizes (for review see Kalechstein et al, 2007;Parrott, 2013), other cognitive domains yielded inconclusive results. The meta-analysis from Laws and Kokkalis (2007) found a medium effect size (d=0.63) for working memory (short-term memory) deficits in recreational MDMA users, but also reported that impairments are likely driven by verbal working memory deficits, whereas visual working memory may be primarily affected by cannabis use.…”
Section: Introductionmentioning
confidence: 99%